Wild Again : The Struggle to Save the Black-Footed Ferret - Jachowski, David, 1977- (Book collections on Project MUSE., 2014)
This engaging personal account of one of America's most contested wildlife conservation campaigns has as its central character the black-footed ferret. Once feared extinct, and still one of North America's rarest mammals, the black-footed ferret exemplifies the ecological, social, and political challenges of conservation in the West, including the risks involved with intensive captive breeding and reintroduction to natural habitat. David Jachowski draws on more than a decade of experience working to save the ferret. His unique perspective and informative anecdotes reveal the scientific and huma.